Economic, Socio-Cultural and Environmental Influences on Relapse of Drug Abuse at the Pelita Jiwa Insani Padang Foundation - Netdrawati Netdrawati; Heldi Heldi; Nurhasan Syah; Erianjoni Erianjoni (Postgraduate, University of Mataram, 2023)
One way to recover from drug abuse is by facilitating free rehabilitation. However, even though they have undergone rehabilitation to get rid of drug addiction, quite a few of them have a tendency to use drugs again. This research was conducted at the Pelita Jiwa Insani Foundation, Padang. This research was conducted in November 2023. This research uses a quantitative and qualitative approach with a descriptive design in the form of a case study. Data were collected using questionnaires and research checklists as well as observation guides. The research results showed that 100% of all informants stated that they had been using drugs for a long time. Their habit of using drugs stems from a process of curiosity and continuing to try drugs. Furthermore, the economic influence shows that of the 10 respondents studied, 6 respondents had high economic status and were working and experienced a relapse and 4 respondents had low status and did not work and experienced a relapse. The socio-cultural influence on the curiosity aspect of using drugs has a percentage of 70%. In the prestige aspect, the percentage is 20%. In the aspect of drug use to increase stamina, the percentage is 80%. Meanwhile, the aspect of eliminating boredom received a percentage score of 70%. Family, community and peer environment factors can cause relapse